Gestational Diabetes and Preeclampsia in Association with Air Pollution at Levels below Current Air Quality Guidelines - Malmqvist, Ebba (National Institute of Environmental Health Sciences, 2013)
Background: Several studies have estimated associations between air pollution and birth outcomes, but few have evaluated potential effects on pregnancy complications. Objective: We investigated whether low-level exposure to air pollution is associated with gestational diabetes and preeclampsia. Methods: High-quality registry information on 81,110 singleton pregnancy outcomes in southern Sweden during 1999–2005 was linked to individual-level exposure estimates with high spatial resolution. Modeled exposure to nitrogen oxides (NO(x)), expressed as mean concentrations per trimester, and proximity to roads of different traffic densities were used as proxy indicators of exposure to combustion-related air pollution. The data were analyzed by logistic regression, with and without adjusting for potential confounders. Results: The prevalence of gestational diabetes increased with each NO(x) quartile, with an adjusted odds ratio (OR) of 1.69 (95% CI: 1.41, 2.03) for the highest (> 22.7 µg/m(3)) compared with the lowest quartile (2.5–8.9 µg/m(3)) of exposure during the second trimester. The adjusted OR for acquiring preeclampsia after exposure during the third trimester was 1.51 (1.32, 1.73) in the highest quartile of NO(x) compared with the lowest. Both outcomes were associated with high traffic density, but ORs were significant for gestational diabetes only. Conclusion: NO(x) exposure during pregnancy was associated with gestational diabetes and preeclampsia in an area with air pollution levels below current air quality guidelines.